Економіко-математичне моделювання впливу інвестиційного податкового кредиту на інвестиційну діяльність суб’єктів економічних відносин - Рекова, Н.Ю.; Стичінська, О.О. (Економіка промисловості, 2012)
Проведено аналіз сучасних досліджень щодо впливу інвестиційного податкового кредиту на інвестиційну діяльність суб’єктів економічних відносин. Виявлено обмеженість їх використання в умовах, перманентних у соціально-економічному середовищі України. Розроблено нову модель фінансового регулювання інвестицій та обґрунтовано доцільність упровадження інвестиційного податкового кредиту в податкове законодавство України.
Ключові слова: інвестиційний податковий кредит, інвестиційна діяльність суб’єктів економічних відносин, фінансове регулювання, інвестиції, податкове законодавство. Проведен анализ современных исследований влияния инвестиционного налогового кредита на инвестиционную деятельность субъектов экономических отношений. Выявлена ограниченность их использования в условиях, перманентных в социально-экономической среде Украины. Разработана новая модель финансового регулирования инвестиций и обоснована целесообразность внедрения инвестиционного налогового кредита в налоговое законодательство Украины.
Ключевые слова: инвестиционный налоговый кредит, инвестиционная деятельность субъектов экономических отношений, финансовое регулирование, инвестиции, налоговое законодательство. It has been carried out the analysis of modern studies of the effect of the investment tax credit on investment activity of economic agents. It refers to the study of neoclassical economic school in economic and mathematical modelling of the impact of taxation on economy, and foreign scientists rese¬arches, such as R. Barro, Ks. Sala-i-Martin, R. King and S. Rebelo, namely the basic provisions of the neoclassical economic theory from the standpoint of research of influence of the investment tax credit on the economic activity of economic agents.
The results of the model in terms of stability in 2011 showed that the instruments used in the tax legislation in present conditions do not meet the needs of sustainable development of investment policy in Ukraine. Their using promotes insignificant positive changes in key macroeconomic indicators of the state economy. It calls for introduction of the study of investment tax credit in tax legislation and financial regulation of Ukraine.
As a result of the optimization model calculations has been obtained the optimal rate of the investment tax credit of 4,5%, and the optimal time of providing – 5 years. In such circumstances, for the entire period of calculation the output of productions increased 1,5 times, tax revenues – 1,7 times, the value of assets – 1,4 times, and the number of employed – 1,2 times.
Therefore Ukraine's economy needs to be improved by fiscal instruments of financial regulation of investment, namely investment tax credit. It contributes to both the output and tax revenues, which is beneficial for both the economic agents and the state as a whole. The implementation of the investment tax credit in the tax legislation and financial regulation of Ukraine in the context of promoting investment activity will create new conditions for sustainable economic development.
Further direction for research is developing of recommendations for the development of investment policy in the Ukrainian economy from the standpoint of enterprise income tax.
Keywords: investment tax credit, investment activity of economic agents, financial regulation, investment, tax legislation.